A survey of knowledge about health education and self-management behavior in 118 patients with early diabetic nephropathy (118例早期糖尿病肾病患者健康教育知识水平及自我管理行为现状调查) - CHEN Furong (陈芙蓉); ZHOU Jianping (周建平); MAO Dandan (毛丹旦); BO Jing (薄静); ZHUANG Ji (庄姬) (中西医结合护理)
Objective To investigate the knowledge about health education and self-management behavior in patients with early diabetic nephropathy, and provide reference for establishment of targeted health education and nursing plan. Methods A convenience sample of 118 patients with early diabetic nephropathy was enrolled. The general information, patients’ knowledge about health education and their self-management behavior were assessed by self-made Knowledge Assessment Scale and the Summary of Diabetes Self-Care Activities Measure(SDSCA). Results The average score of lifestyle dimension of Knowledge Assessment Scale was (2. 58±0. 59), and the lowest score was reported in diet sub-dimension(2. 29±0. 56), followed by exercise(2. 59±0. 69), stopping smoking (2. 96±0. 88) , stopping alcohol (3. 17±0. 95)and bodyweight control (3. 33±0. 93). The average score of medication management dimension was (3. 11±0. 65), and average score of symptoms observation and nursing practice was (2. 55±0. 73)and (2. 55±0. 89), respectively. The average score of social-psychological nursing and follow-up management was (3. 28±0. 60)and (3. 28±0. 60), respectively. The score of each dimension of SDSCA was listed as follows: diet (3. 39±1. 30), exercise (4. 05±2. 85), blood sugar monitoring(1. 14±1. 82), medication adherence(4. 20±2. 30)and foot care(1. 87±2. 47). There were 39(33. 05%)smokers who consumed averaged 19. 01 cigarettes per day. Conclusion Patients with early diabetic nephropathy had poor knowledge about health education, practically in knowledge about diet and exercise. Efforts should be made to enhance the health education on knowledge about prevention and treatment of early diabetic nephropathy. In addition, the poor self-management behavior among patients with early diabetic nephropathy may indicate poor diabetes self-management as a negative influencing factor of progression of early diabetic nephropathy. (目的 探讨早期糖尿病肾病患者健康教育知识水平及自我管理行为现状, 为制定针对性的健康教育及护理方案提供依据。方法 采用便利抽样方法对纳入某三级甲等中医院符合纳入排除标准的118例早期糖尿病肾病患者实施调查, 调查内容包括患者一般资料、自编的早期糖尿病肾病相关知识知晓情况调查表、糖尿病自我管理活动问卷(SDSCA), 并对数据资料进行描述性统计分析。结果 早期糖尿病肾病患者健康教育知识水平调查结果显示, 生活方式平均得分(2. 58±0. 59)分, 其中饮食(2. 29±0. 56)分、运动(2. 59±0. 69)分、戒烟(2. 96±0. 88)分、戒酒(3. 17±0. 95)分、体质量控制(3. 33±0. 93)分; 用药管理平均得分(3. 11±0. 65)分, 症状观察(2. 55±0. 73)分, 护理操作技巧(2. 55±0. 89)分; 社会心理护理(3. 28±0. 60)分, 复诊管理(3. 24±0. 96)分; SDSCA量表的各维度中得分为饮食(3. 39±1. 30)分、运动(4. 05±2. 85)分、血糖监测(1. 14±1. 82)分、遵医用药(4. 20±2. 30)分和足部护理(1. 87±2. 47)分。39(33. 05%)人吸烟, 平均每日吸烟19. 01支。结论 早期糖尿病患者的健康教育知识水平知晓情况较差, 尤其是生活方式中的饮食及运动方面, 早期糖尿病肾病防治的相关知识的宣传教育和科普亟待加强; 此外, 早期糖尿病肾病患者的自我管理行为也较差, 可能进一步验证了不良的糖尿病自我管理是早期糖尿病肾病疾病进展的重要因素。)